CHINESE GEOGRAPHIC INDICATIONS LAW DURING THE 13-TH AND 14-TH FIVE YEAR PLAN - S. A. Abramov (Теоретическая и прикладная юриспруденция)
The article examines the development of the law of geographical indications of the People’s Republic of China. An attempt is made to determine the relationship between the Confucian legal traditions of Ancient China and the law of geographical indications in China. A special place in the article is occupied by the assessment of innovations in the law of geographical indications of the PRC during the 14th Five-Year Plan, the role of multilateral and bilateral practices of international legal protection of geographical indications.